Hypertension Today: Role of Sports and Exercise Medicine - Laura, Stefani; Gabriele, Mascherini; Benedetta, Tosi; Giorgio, Galanti (Journal of Hypertension and Cardiology, 2019)
Progressive increase of cardiovascular disease (CVD), with a rising costs for the society, is driving to focus on risk’s factors reduction. The importance to prevent acute events and to reduce mortality and morbility have risen the sound of the correct life style indications as the primary approach for hypertension. The new classification of hypertension has amplified an high-value of the role of the physical activity especially in the initial phase of the disease when the potential positive impact of the regular physical activity can permit to avoid the use of the pharmacological treatment. The numbers of the hypertensive subjects is increasing everywhere; however the awareness of the presence of the disease is not so frequent. Although some risk factors, such as age and hereditary factors cannot be changed, on the contrary lifestyle’s modification can prevent the CVD and hypertension. Sports Medicine physicians agree that healthcare providers need to focus on preventive and lifestyle aspects of cardiovascular care to promote individual and population health. A dedicated approach to prescribe the amount of weekly physical activity at moderate intensity can allow to control the blood pressure values avoiding the assumption of antihypertensive drugs. Aerobic and resistance exercises need to be individually established by dedicated models tailored on the basis of the specific characteristics of the people involved. Sports and Exercise Medicine can contributes to manage and to tailor the amount of programmed physical activity starting from the ”exercise prescription” guidelines.
Keywords: cardiovascular disease; hypertension